7 - Dinâmicas dos movimentos juvenis’: protestos nas ruas e contestações nas redes sociais em Angola - Gilson Lazaro, (Africa Development, 2025)
This article examines the protest actions they have triggered by the so- called revús with a view to bringing about social change. The article seeks to understand and describe the relevance of these actions, the type of demands raised, as well as the articulation established at local and national level because of expressions, aspirations, wills, political and social struggles against the authoritarian Angolan political culture. The article essentially discusses two pre-election protests held in Luanda on symbolic dates and three expressive movements, two before and one during the electoral period, which initially emerged on social networks. The text focuses on analyzing the social impact of these events, especially among young Angolans.